Impacts of Industry 4.0 on Malaysian Manufacturing Industries - Lee, Wan Yee; Tan, Seng Teck; Sorooshian, Shahryar (World Scientific and Engineering Academy and Society, 2019)
Industry 4.0 is the fourth industrial revolution which is the new era to the world. However, there are not enough academic knowledge about it. Also, Malaysian manufacturing industries have not enough awareness of the impact of it. Hence, the objective of this research is to identify the main impacts of Industry 4.0 on manufacturing industries in Malaysia. This research is using a quantitative method of analysis, pairwise comparison, and the data collection method was questionnaires which answered by the experts of the industry 4.0 in Malaysia. In the findings, the ranking in the results in order is flexibility, real-time detailed end-to-end product transparency and coordinating real time, etc. Therefore, based on the result of this study,the government can encourage manufacturing companies to implement Industry 4.0 and gain positive impacts.